Problematika Pendekatan Analogi (Qiyas) Dalam Penetapan Hukum Islam (Telaah atas Pemikiran Ibn Hazm dan Ibn Qayyim al-Jawziyah) - Wirman, Hardi Putra (UIN Sunan Kalijaga, 2013)
Existence of qiy?s (analogy) as an effort to dig an Islamic law, it still remains a problem and the debate in a long period of time. Whereas qiy?s is the mainstay of scholars when a problem is not found in the legal status of the Koran, Sunna and ijm?’. In this paper, before authors explore the views and ideas of Ibn Hazm and Ibn Qayyim about qiy?s, authors will describe a little about the views of scholars of Fiqh jumhur against qiy?s position as one of the methods of determination of law in Islam. At the end of the paper, the authors found that the concepts of Ibn Hazm would be very difficult to be followed by the public, because it assumes that the Koran was the final, and the use of reason to interpret something that is absolutely forbidden. While Ibn Qayyim adapted more impressed with the changing times. But liberalism of Ibn Qayyim in using Intellect needs to be addressed and responded wisely. Because, in the absence of control, the use of reason in the sphere arbitrarily Islamic law will also be able to fade the purity of the teachings of Islam itself.